A tale of two scandals: scale shift and the inefficacy of crisis communication management in Olympic scandals - Meier, Henk Erik; Tickell, Samuel; Konjer, Mara Verena (Frontiers in Communication, 2023)
Introduction: Mega sport events, such as, the Olympic Games provide niche sports unique opportunities to attract public attention. However, scandals during these events can pose serious threats for these niche sports. In particular if a sport scandal enables hostile stakeholders to achieve a scale shift, it becomes almost impossible for a niche sport organization to manage the scandal. Methods: The article employs a comparative research design that examines the trajectory of two scandals related to the German Olympic team, which differ wih regard to the occurance of a scale shift. The first scandal involved a racist slur made by German official during a cycling event, the second scandal was a case of animal cruelty during Modern Pentathlon’s equestrian event. Research relies on a mix of qualitative document analyses and quantitative analyses of the German Twitter discourse on both scandals. The analyses focus on the vulnerability to scandals, the potential for contentious politics, the scandal triggering events, the crisis communication, the reception and the outcomes of both scandals. Results and discussion: Our results show the detrimental impact of a scale shift on niche sports. The animal cruelty scandal put the future of Modern Pentathlon at the Olympics at risk and triggered far-reaching reforms. The case supports the idea that a scale shift becomes more likely if there exists an effective collective action frame. In contrast, the German sport organizations effectively ended the racist slur scandal by imposing a limited sanction on the offender.